Physico-Chemical Properties and the Structure of Dermatan Sulfate Fractions Purified from Plasma after Oral Administration in Healthy Human Volunteers - Volpi, Nicola (Thrombosis and Haemostasis, 1996)
Dermatan sulfate (DS) was administered by oral route in healthy human volunteers. The structure, physico-chemical properties and biological activity of DS purified from human plasma after oral administration were studied and compared with those of native DS.DS extracted and purified from pig mucosa has a relative molecular mass (Mr) of about 23,100 and is composed of about 10% nonsulfated disaccharide, 80% monosulfated disaccharides and about 10% disulfat-ed disaccharides, with a sulfate to carboxyl ratio of 1.00 and a heparin cofactor II (HCII) activity of about 160 units/mg. This native polysaccharide is composed of about 94% iduronic acid.One gram of native DS was orally administered to five healthy human volunteers, and 50 ml of blood were collected after 4 h. DS possibly present in plasma after oral administration was extracted and purified. About 130 ± 42 Μg of DS per 50 ml of blood were detected by agarose-gel electrophoresis and DMB assay. This DS shows a broad Mr range. After oral absorption, substantial amounts of species with a Mr of about 7,500 are detected in blood but chains with Mr ranging from 7,500 to 20,000 are also found. Moreover, some very low-Mr species are detected, with a prevalence of disaccharides. After oral absorption, DS is sulfated above all in position 4 of the N-acetyl-galactosamine (60%), with a sulfate to carboxyl ratio of about 0.64, demonstrating that DS is desulfated during or after oral absorption by about 30-40%. A small amount of disulfated disaccharide (in particular 2,4-disulfated, 1.4%) is preserved from catabolic processes, as DS extracted from human plasma is able to inhibit thrombin activity mediated by HCII (about 16 U/mg).